Religious Accommodation in Bioethics and the Practice of Medicine - Smith, William R (J Med Philos, 2021)
Debates about the ethics of health care and medical research in contemporary pluralistic democracies often arise partly from competing religious and secular values. Such disagreements raise challenges of balancing claims of religious liberty with claims to equal treatment in health care. This paper proposes several mid-level principles to help in framing sound policies for resolving such disputes. We develop and illustrate these principles, exploring their application to conscientious objection by religious providers and religious institutions, accommodation of religious priorities in biomedical research, and treatment of patients’ religious views in doctor–patient encounters. Given that no sound set of guiding principles yields precise solutions for every policy dispute, we explore how morally sound democracies might deliberatively resolve such policy issues, following our proposed principles. Taken together and carefully interpreted, these principles may help in guiding difficult decision making in the indefinitely large realm where government, medical providers, and patients encounter problems concerning religion and medicine.